Toxicity of oil spill response agents and crude oils to five aquatic test species. (April 2020) - Barron, Mace G.; Bejarano, Adriana C.; Conmy, Robyn N.; Sundaravadivelu, Devi; Meyer, Peter
Abstract: The majority of aquatic toxicity data for petroleum products has been limited to a few intensively studied crude oils and Corexit chemical dispersants, and acute toxicity testing in two standard estuarine test species: mysids ( Americamysis bahia ) and inland silversides ( Menidia beryllina ). This study compared the toxicity of two chemical dispersants commonly stock piled for spill response (Corexit EC9500A®, Finasol®OSR 52), three less studied agents (Accell Clean®DWD dispersant; CytoSol® surface washing agent; Gelco200® solidifier), and three crude oils differing in hydrocarbon composition (Dorado, Endicott, Alaska North Slope). Consistent with listings on the U.S. National Contingency Plan Product Schedule, general rank order toxicity was greatest for dispersants and lowest for the solidifier. The results indicate that freshwater species can have similar sensitivity as the conventionally tested mysids and silversides, and that the sea urchin ( Arbacia punctulata ) appears to be a reasonable addition to increase taxa diversity in standardized oil agent testing. Highlights: The toxicity of spill response agents and crude oils was assessed in five aquatic species. General rank order toxicity of was greatest for dispersants and lowest for the solidifier. Freshwater species had similar sensitivity as the conventionally tested mysids and silversides. The sea urchin test can provide additional taxa diversity to standardized oil agent testing.